KALIKHA empowering the Filipino animation industry through an animation incubator - Umipig, Seth Ephraim G.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The Filipino animation industry has been producing high quality animated media for
over four decades. Despite all its talent however, it is heavily reliant on outsourced
projects from foreign studios, hindering the development of original Filipino animated
media. Local studios are therefore designed to maximize the mechanized production, required by these outside studios, limiting the creative work of artists. By focusing on
the intersection of architecture and animation, this study explores how the design of
an animation studio incubator can empower local studios to transition from
mechanized animation production to creative processes. Set within the context of
Quezon City's Knowledge-Business District, this project capitalizes on its proximity to
media hubs and adjacent creative industries, offering a strategic location for an
animation incubator. Using a mixed-method approach, the research integrates
descriptive studies to identify spatial requirements for animation studios and
phenomenological studies to understand the creative processes of animators. Findings
of the study are applied in the architectural design through several approaches such
as creative placemaking and spatial sequencing, all aimed at creating a dynamic and
adaptive environment for animators. Preliminary findings highlight the need for
creative spaces: rooms for personal work, stations for collaborative meetings, areas
for presentation and making spaces. The animation incubator seeks to bridge gaps in
the industry by incubating ideas, enhancing creativity, and providing a platform for
Filipino animators to produce globally competitive content. This undertaking not only
contributes to the architecture field by exploring its intersection with animation but
also supports the national agenda of transitioning to a knowledge-based economy,
highlighting architecture's potential to influence economic and cultural growth.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Animation; Animators, Filipino; Animation studios